Clinical Questions and Answers on Gastrointestinal Endoscopy during the Novel Coronavirus Disease 2019 pandemic. Issue 5 (9th July 2020) - Furuta, Takahisa; Irisawa, Atsushi; Matsumoto, Takayuki; Kawai, Takashi; Inaba, Tomoki; Kanno, Atsushi; Katanuma, Akio; Kawahara, Yoshiro; Matsuda, Koji; Mizukami, Kazuhiro; Otsuka, Takao; Yasuda, Ichiro; et al.
Abstract : Some situations may require endoscopy during the COVID‐19 (Coronavirus Disease 2019) pandemic. Here, we describe the necessary precautions in the form of clinical questions and answers (Q&A) regarding the safe deployment of gastrointestinal endoscopy in such situations while protecting endoscopy staff and patients from infection. Non‐urgent endoscopy should be postponed. The risk of infection in patients should be evaluated in advance by questionnaire and body temperature. The health of staff must be checked every day. Decisions to employ endoscopy should be based on the institutional conditions and aims of endoscopy. All endoscopic staff need to wear appropriate personal protective equipment (PPE). The endoscope and other devices should be cleaned and disinfected after procedures in accordance with the relevant guidelines. Optimal management of the endoscopy unit is required. Endoscopy for infected patients or those with suspected infection demands exceptional caution. When a patient who undergoes endoscopy is later found to have COVID‐19, the members of staff involved are considered exposed to the virus and must not work for at least 14 days if their PPE is considered insufficient. When PPE resources are limited, some equipment may be used continuously throughout a shift as long as it is not contaminated. Details of the aforementioned protective measures are described.